Storm alert : understanding weather disasters - Aylesworth, Thomas G. (Messner certified editions, 1980)
Examines certain weather conditions, including thunderstorms, hurricanes, and avalanches, which frequently cause extensive damage and loss of life. Also describes what to do if caught in the conditions.